Establishment Of Backup Components Through Government Communication In The Digital Age - Darmawan, Tjetjep; Putriana, Muria (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
Government communication through social media has become a significant phenomenon in the digital age. This research summarizes the strategies, objectives and impact of government communication on social media platforms such as twitter, Instagram, facebook and so on. The research method used is a qualitative method by conducting surveys with data analysis techniques through triangulation. The results of discussions and conclusions through data analysis both by observation and online interaction that the government must be able to use social media to increase public engagement, convey policies and respond to important issues regarding the policies of the government itself, although effective in reaching a broad audience, challenges including crisis management that urgently need to be anticipated, as well as narrative control systems and sustainable participation society in national builders. In the future, this research can be further needed to understand the dynamics of the evolution of government communication in this digital era.